Prostitution x STD/AIDS: a descriptive study with perspective on practices of prevention - Moura, Ana Débora A.; Lima, Guldemar G de; Farias, Leiliane M.; Feitoza, Aline R.; Barroso, Maria Grasiela T. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: sexually transmitted diseases (STDs) are considered occupational hazard for prostitutes, which can be prevented with condom use. Objective: this study aims to report how prostitutes from a municipality in the state of Ceará are preventing STD/aids and how they are included in STD/ aids prevention programs proposed by the National Program of STD/HIV/aids. Methods: this is an exploratory and descriptive study of qualitative nature. The data collection was carried out by means of self-report technique, and the instruments used were participant observation and non-structured interviews. Performed with 30 prostitutes in a municipality in the countryside of the state of Ceará in the period between 2000 and 2002. The data collected were organized into four topics: profile of prostitutes, condom use by prostitutes, condom use by partners, and STDs as reality, and analyzed based on relevant literature. Results: it is possible to check that women enter prostitution as teenagers, low level of information of these women who use sex to survive, and not using condoms in all sexual relations, minimizing prevention practices of the STD/aids. Conclusion: it is necessary that responsible organizations elaborate strategies whose aim is to give option and support for adolescents, so that they do not start very early in the prostitution line. All the factors and determinants which cause this problem must be emphasized. Besides, school and professionalization, decent work conditions and an income source for their own sustenance and the sustenance of their families.